NAHDLATUL ULAMA, TOKOHNYA KEGIATAN DALAM DUNIA PENDIDIKAN DAN PERKEMBANGAN TEKNOLOGI INFORMASI - Kamal; Rama, Bahaking; Siraj, Arifuddin (TEKNOS: Jurnal Pendidikan dan Teknologi, 2023)
NU educational institutions have spread throughout Indonesia. Through literature review research methods and a qualitative approach, this article analyzes various relevant sources. The contribution of NU educational institutions can be seen in providing quality education and in-depth religious knowledge, as well as spreading moderate Islamic values. NU's educational concept is based on the teachings of Ahlusunnah Wal Jama'ah (Aswaja) and an inclusive learning method approach. Important figures in the world of NU education such as KH Hasyim Asy'ari, KH Abdul Wahid Hasyim, and KH Abdul Wahab Chasbullah were also appointed. NU education does not only focus on intellectual aspects, but also the development of moderate morals, ethics and Islamic values. Through this education, NU produces a generation that is competitive, has noble character, and is able to make a positive contribution to Indonesian society. In this summary, emphasis is placed on the important role and contribution of NU in the development of education in Indonesia. Nahdlatul Ulama (NU), which is the largest Islamic organization in Indonesia, can be said to be quite late in responding to the digital era when compared to other Islamic groups. The digital era is an era that we cannot avoid, in fact we as humans will continue to develop according to the times. Therefore, we also have to adapt to be more advanced. In response to this, our NU began to exist to develop by using technology.